Effect of lead on biofilm formation by environmental isolates of Bacillus spp. - Jenan Atiyah Ghafil; Ayaid Khadem Zgair; Shaymaa Hussein Hassan; Walaa Najim Abd alwahed (World Journal of Experimental Biosciences, 2016)
Biofilm formation is one of the biggest challenges of scientists. Role of heavy metals in forming biofilm is not clear enough. Here, the effect of lead on biofilm formation by Bacillus spp. isolated from soil in terms of biofilm formation and remove was studied. In present study, 10 isolates of Bacillus spp were isolated from soil. The ability of all isolates to form biofilm was evaluated. The effect of lead on biofilm formation was studied by adding lead (pb) before forming biofilm. In another experiment the lead was added after biofilm formation to study the effect of lead on biofilm remove. The current study, showed the ability of all studied isolates to form biofilm. Maximum biofilm formation by Bacillus spp isolate number 8 (B8) followed by B1 and B3. The lowest biofilm formation was found in case of isolate 4 (B4). The lead (50 ppm) reduced biofilm formation by B8, B1 and B3 isolates when the lead was used before biofilm formation (P
Keywords: Bacillus, Biofilm, Heavy metals, Lead.